2007
DOI: 10.1253/circj.71.868
|View full text |Cite
|
Sign up to set email alerts
|

Serum Resistin as a Biological Marker for Coronary Artery Disease and Restenosis in Type 2 Diabetic Patients

Abstract: BackgroundResistin is an adipocyte-secreted hormone. The relationship between circulating resistin concentrations and atherosclerotic coronary artery disease (CAD) in type 2 diabetic patients, if any, remains poorly understood. Serum resistin concentrations were investigated in type 2 diabetic patients with CAD (DMCAD), and compared with the concentrations in diabetics patients without CAD (diabetes mellitus, DM). Whether resistin levels are associated with increased restenosis rates in diabetic patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 24 publications
2
29
0
5
Order By: Relevance
“…Hoefle et al were in agreement with the last 2 authors and reported no significant increase in plasma resistin levels in coronary stenosis (14). On et al found higher resistin levels in CAD in type 2 diabetes mellitus (15). In another study, the severity of CAD was represented as the number of stenoses in coronaries.…”
Section: Discussionsupporting
confidence: 68%
“…Hoefle et al were in agreement with the last 2 authors and reported no significant increase in plasma resistin levels in coronary stenosis (14). On et al found higher resistin levels in CAD in type 2 diabetes mellitus (15). In another study, the severity of CAD was represented as the number of stenoses in coronaries.…”
Section: Discussionsupporting
confidence: 68%
“…In vitro, resistin was reported to promote human smooth muscle cell proliferation 8) ; therefore, resistin may play a role in the development of restenosis associated with neointimal proliferation. Recently, On et al 18) reported resistin levels to be higher in 35 diabetic patients who developed restenosis than in 35 diabetic patients who did not 18) ; however, no correlation was found between Kaplan-Meier analysis demonstrated a lower event-free survival rate in patients with a resistin level of 4.0 ng/mL than in those without (p 0.001). resistin levels and the severity of restenosis.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, Yamawaki et al demonstrated a vasodilating effect of omentin on isolated blood vessels, suggesting omentin involvement in endothelial function [14] . There have been several reports showing that other adipokines, such as adiponectin [15][16][17] , resistin [17][18][19][20] , leptin [19] , visfatin [21][22][23] , TNF-α [24] , and IL-6 [25] , are related to inflammation and coronary artery disease (CAD). We hypothesized that omentin-1 might be implicated in CAD due to a possible association with inflammation and endothelial function.…”
Section: Introductionmentioning
confidence: 99%